The Role of House Fly Musca domestica in transmitting the Intestinal Parasites for Human - Shujan R. Hassan; Rajaa M. Ismeel (Tikrit Journal of Pure Science)
The present study is made up during October 2014 till March 2015 to know the parasitic stages which are carried out by different part  Musca domestica. The samples are collected from five different places which are included the restaurants, schools , kitchens, grid sewage and wild land. The number of the samples which are examined is reached 100 samples, all of them were examined by direct smear using the physiological solution and lugal iodine solution by flotation way and by using saturated zinc sulfide solution and diagnosed four species of intestinal parasites which are Entamoeba coli, Entamoeba histolytic, Giardia lamblia ,Trichomonas hominess .